Mental health service users' progression from illicit drug use to schizophrenia in New Zealand. Issue 5 (5th September 2019) - Mellsop, Graham; Tapsell, Rees; Holmes, Pragya
Abstract : Background: Recently, publications have hypothesised that the demonstrated increase in the incidence of schizophrenia in New Zealand is a side effect of the increased strength of available cannabis derivatives over the last 25+ years and the much more recent increase in the population's use of methamphetamine. Aim: To compare the rates of later schizophrenia between age-matched mental health service users with initial diagnoses as alcohol abusers or illicit drug users. Method: From the PRIMHD comprehensive national database, all users of the mental health services over a 5-year period who received an ICD-10 presenting diagnosis of alcohol or substance use/abuse were identified. For each person identified, the database was examined for the following 3 years to determine the numbers later diagnosed with schizophrenia. Results: For the initial alcohol problem people in their twenties, 1.7% were diagnosed as suffering from schizophrenia in the subsequent 3 years. For the initial drug problem people, the rate was 10.9%. Within that drug-using population, the indigenous Maori developed schizophrenia at a higher rate than did the remainder of the population. Conclusion: These findings in New Zealand require further research into their generalisability, context and explanation.